SUÇ VE CEZA: BATMAN ÜÇLEMESİ ADALETİN HEDEF KİTLE ALGISI - Feryal ÇUBUKÇU (Fırat University, 2019)
Film scholars debate whether mainstream Hollywood film industry creates social values or merely reflects social values, or even creates and then reflects social values, which leads to the fact that films inarguably resonate with their socio-historical-economic moment. Culture shapes media even as media shapes culture. The role of media in public perceptions and understandings of crime and justice issues cannot be underestimated. While films do not purport to be truthful, they seek to create a kind of reality that audiences will accept as credible and valid. This study aims at exploring primarily what the relationship is between law, language and film, with the emphasis on how crimes are constructed, how victimization is represented and how justice is treated in the comics especially the Batman series by Christopher Nolan.